Evaluation of rapidly mutating Y-STRs in Pakistani population. Issue 1 (December 2019) - Farhatullah, M.; Absar, M.; Rauf, S.; Tracy, M.; Almulla, H.; Almheiri, R.; Adam, A.; Alghafri, R.; Khan, MR.
Abstract: Y-chromosomal Short Tandem Repeats have been widely used in forensic investigations, identification of males for criminal justice purpose and population genetics. Commercially available Y-STRs kits allow the identification of male pedigrees and has a limited application in forensic genetics because of its limitation in differentiating closely related male individuals. Recent research with the Rapidly Mutating Y-STRs (RM Y-STRs) have revealed that these loci deliver significantly higher discrimination capacity and haplotype diversity in worldwide populations when compared with the conventional Y-STRs. Although a number of RM Y-STRs have found their way in most updated commercial kits, there are still some loci that are not yet used in such kits. The aim of this study is to develop RM Y-STR haplotypes frequency database for the Pakistani population, in order to appraise the resolution power of these loci. A total of 212 unrelated males from the Pakistani population were typed with 13 RM Y-STRs which comprise DYF399S1, DYF387S1, DYS570, DYS576, DYS518, DYS526a + b, DYS626, DYS627, DYF403S1a + b, DYF404S1, DYS449, DYS547 and DYS612. 211 unique haplotypes were identified, out of which 1 haplotype was shared between two individuals, accounting for 0.9952 discrimination capacity (DC). Haplotype diversity was found to be 0.999925. Gene diversity (GD) values of all the loci were higher than 0.5, where the highest GD values were observed at DYF399S1, DYF403S1a and DYF404S1; with values of 0.99419, 0.98252 and 0.93061 respectively. Results of our study revealed that these 13 RM Y-STRs produced significantly stronger discriminatory power in Pakistani populations.